Solid-state photoelectrochemical cell with TiO2 nanotubes for water splitting. Issue 1 (6th September 2016) - Xu, Kaiqi; Chatzitakis, Athanasios; Norby, Truls
Abstract : We have fabricated and tested a photoelectrochemical (PEC) cell where the aqueous electrolyte has been replaced by a proton conducting hydrated Nafion® polymer membrane. Abstract : We have fabricated and tested a photoelectrochemical (PEC) cell where the aqueous electrolyte has been replaced by a proton conducting hydrated Nafion® polymer membrane. The membrane was sandwiched between a TiO2 -based photoanode and a Pt/C-based cathode. The performance was tested with two types of photoanode electrodes, a thermally prepared TiO2 film on Ti foil (T-TiO2 ) and a nanostructured TiO2 films in the form of highly ordered nanotubes (TNT) of different lengths. Firstly, photovoltammetry experiments were conducted under asymmetric conditions, where the anode was immersed in deionized water, while the cathode was kept in ambient air. The results showed a high incident photon-to-current efficiency (IPCE) of 19% under unassisted conditions (short-circuit, 0 V vs . cathode) with short TNT ( ca . 1 μm) under 4 mW cm −2 illumination with UV-A rich light. Secondly, the deionized water was replaced by 0.5 M Na2 SO4 and now the performance was higher with longer nanotubes, assigned to increased ionic conductivity inside the tubes. An unassisted (0 V) IPCE of 33% was achieved with nanotubes of ca . 8 μm. The presented solid-state PEC cell minimizes the electrode distance and volume of the device, and provides a way towards compact practical applications in solar water splitting.